INFORMATION SECURITY IN SMART TOURISM: RISK MANAGEMENT, MARKETING STRATEGIES, PERSPECTIVES - RUDENKO, Mykola; KOCHUMA, Inna; KRAVCHENKO, Olena; TRETYAK, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines information security in smart tourism and offers risk management tools, marketing strategies, and prospects.The main elements of Smart-tourism are outlined, among which Smart-infrastructure (the use of the Internet of Things (IoT), artificial intelligence, sensors, cameras and other technologies to improve the management of tourist attractions and services), Smart-mobility (development and distribution of mobile applications) , which allow tourists to quickly find information about transport, routes, places of interest, etc.), Smart-communication (use of messengers, chatbots and other means of communication to provide information and support to tourists), Smart-marketing (use of digital platforms for advertising tourist services and attraction of new customers, personalized services, interactive technologies), Smart ecology (development of environmental protection technologies and support of environmental initiatives in the field of tourism).The component composition of Smart-tourism, which is based on the accumulation, exchange and processing of large arrays of information with the use of information and communication technologies, is highlighted. "Smart direction" involves the integration of information and communication technologies into the physical tourist infrastructure. "Smart business" means the digitalization of core processes and the creation of a complex ecosystem. The smart experience component is about improving and enriching the experience through personalization, real-time monitoring.It was revealed that the primary task in the way of ensuring information security in Smart-tourism is to identify the causes of unauthorized access to information, assess threats to the information security of its subjects and create powerful systems for its protection. A comprehensive system of information security of a tourist enterprise was built, detailing its elemental composition, and it was stated that protection should be carried out at all stages of the life cycle of information, taking into account the latest trends and phenomena in the field of digital technology development.
Keywords: information security; smart tourism; digitalization; cyber security; tourist enterprises; smart marketing; digital technologies; risk management; marketing strategies